Drug repurposing in cancer neuroscience: From the viewpoint of the autophagy-mediated innervated niche - Shi, Jiayan; Xu, Jia; Li, Yang; Li, Bowen; Ming, Hui; Nice, Edouard C.; Huang, Canhua; Li, Qifu; Wang, Chuang (Frontiers in Pharmacology, 2022)
Based on the bidirectional interactions between neurology and cancer science, the burgeoning field "cancer neuroscience" has been proposed. An important node in the communications between nerves and cancer is the innervated niche, which has physical contact with the cancer parenchyma or nerve located in the proximity of the tumor. In the innervated niche, autophagy has recently been reported to be a double-edged sword that plays a significant role in maintaining homeostasis. Therefore, regulating the innervated niche by targeting the autophagy pathway may represent a novel therapeutic strategy for cancer treatment. Drug repurposing has received considerable attention for its advantages in cost-effectiveness and safety. The utilization of existing drugs that potentially regulate the innervated niche via the autophagy pathway is therefore a promising pharmacological approach for clinical practice and treatment selection in cancer neuroscience. Herein, we present the cancer neuroscience landscape with an emphasis on the crosstalk between the innervated niche and autophagy, while also summarizing the underlying mechanisms of candidate drugs in modulating the autophagy pathway. This review provides a strong rationale for drug repurposing in cancer treatment from the viewpoint of the autophagy-mediated innervated niche.